Senso comune, buon senso, and Philosophy in Gramsci - Jackson, Robert P. (International Gramsci Journal, 2024)
The vast and intricate theoretical development of Gramsci’s concept of senso comune intersects with diverse themes in his thought, from hegemony and political parties to civil society, the state, and the role of intellectuals, to name but a few. This article contributes to the analysis of the concepts of senso comune and buon senso in Gramsci’s pre-prison writings, Prison Letters, and Prison Notebooks, through its relationship with the development of his conception of philosophy. Engaging with the recent season of historico-philological studies of Gramsci’s writings to pursue the diachronic development of Gramsci’s conception of senso comune, this investigation reconsiders prevailing anglophone «images» of his thought, in relation to senso comune, in light of the resources of the critical editions of Gramsci’s writings. While acknowledging the pitfalls of the unmediated and de-contextualised application of Gramsci’s ideas to the present, this study suggests that a philological reading of Gramsci’s conception of senso comune has value as a pre requisite for a «dialogue with the present», and a strategic analysis of the contemporary conjuncture.